Vascular Abnormalities in Alternating Hemiplegia - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2006)
Skin and/or muscle biopsies in 4 patients, ages 18 months, 8, 9, and 16 years, with alternating hemiplegia of childhood (AHC) were examined by electron microscopy and compared with healthy controls in a study at University Hospital, Lille, France.